Structural Vaccinology: A Three-dimensional View for Vaccine Development - Cozzi, Roberta; Scarselli, Maria; Ilaria Ferlenghi, Ilaria Ferlenghi (Current Topics in Medicinal Chemistry, 2013)
The Structural Vaccinology (SV) approach is the logical evolution of Reverse Vaccinology: a genome-based approach combined with structural biology, with the idea that protective determinants can be used to selectively engineer the antigens that can be re-designed and simplified for inclusion in vaccine combinations. The final objectives of the rational structure-based antigen optimization are the facilitation of industrial-scale production of the antigens combination, obtain a greater immunogenicity and a greater safety profile and finally expand the breadth of protection. Structural Vaccinology is particularly powerful in case of antigenic variation between closely related strains and species. Several examples are available in literature of how SV has already been applied successfully to several bacterial and viral projects. The examples of structure-based antigens optimization reviewed here describe different template procedures that can be followed to develop improved vaccines against other pathogens and potentially help resolve challenges in manufacturing or efficacy.
Keywords: OspA